2003
DOI: 10.1159/000072386
|View full text |Cite
|
Sign up to set email alerts
|

Does Chronic ST Segment Elevation following Q Wave Myocardial Infarction Exclude Tissue Viability?

Abstract: Purpose: Electrocardiographic (ECG) ST segment elevation lasting 2 or more weeks following Q wave myocardial infarction has been associated with ‘ventricular aneurysm’ and absence of tissue viability. Regional systolic dysfunction may reflect either viable myocardium or scar. Positron emission-tomographic (PET) imaging can distinguish viable from nonviable tissue. We hypothesized that patients with chronic ST segment elevation after Q wave infarction might demonstrate salvageable myocardium in the infarct regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Other authors have suggested that persistent STE, in the setting of reperfused infarction, may be ascribed to residual ischemia arising from areas of viable myocardium at the boundary of necrotic regions [27]. However, in our study this explanation seems to be unlikely, as patients with STE showed transmural necrosis in about 90% of cases, making the presence of viable myocardium in this setting highly unlikely [15].…”
Section: Discussioncontrasting
confidence: 53%
“…Other authors have suggested that persistent STE, in the setting of reperfused infarction, may be ascribed to residual ischemia arising from areas of viable myocardium at the boundary of necrotic regions [27]. However, in our study this explanation seems to be unlikely, as patients with STE showed transmural necrosis in about 90% of cases, making the presence of viable myocardium in this setting highly unlikely [15].…”
Section: Discussioncontrasting
confidence: 53%
“…using PET scan, chronic ST elevation after Q wave anterior myocardial infarction did not exclude viability. [13]…”
Section: Discussionmentioning
confidence: 99%